Prevalence and level of stress among final-year students at a health science institute in Bangladesh - Md. Jonaied Alam; Mahmudul Islam Khan Pratik; Abid Hasan Khan; Muhammad Shahidul Islam; Muhammad Millat Hossain (Discover Mental Health)
Abstract Background Final-year students studying in various health science institutes are usually very stressed about their studies so that they can complete their studies without any hurdles. This stress can lead to poor academic and professional results because psychological issues such as anxiety and depression are frequently overlooked and not treated. This study aimed to measure the prevalence of stress and also assess the level of stress symptoms among the final year students of health science institute in Bangladesh. Methods A prospective cross-sectional study involving 134 final-year students of Bangladesh Health Professions Institute (BHPI), which is a well-known health science institute in Bangladesh measured the prevalence of stress and assessed the level of stress symptoms using the Academic Stress Scale (ASS-40). Data was collected through face-to-face interviews and analysed using SPSS software 25.0. Descriptive and inferential statistics were used to analyse the data retrieved from the students. The Pearson correlation coefficient was used to find any deep relation between the levels of stress symptoms of the students with their age. Results The prevalence of stress symptoms among the 134 students was 68.60%. The scenario of having stress symptoms was higher among male students and factors like fear of failure (29.20%), followed by teacher-student relationship/teaching method (28.80%) with addressable factors including personal inadequacy (25.50%) working as a stressor for this students. A negligible association (p > 0.05) was found between the age and the level of stress of the students. Conclusion More than two-thirds of the students experienced stress symptoms during the final days in their institutions. This implies that the educational system, means of teaching, teaching materials, teachers as well as the services provided by the institutions cannot provide a conducive environment for effective learning as well as creating a secure future for the students as long as they can cope with the academic pressure. A student's educational career is being nipped in the bud due to the weak system of our education and institutional system.